PENINGKATAN PENGUASAAN ISTILAH JURNALISTIK MELALUI MODEL DISKUSI DENGAN INFOGRAFIK DINAMIS (DIDIN MANIS) - Muttaqin, Khoirul; Ari Ambarwati (Universitas Islam Malang, 2023)
Journalistic theory is one of the courses given to students of the Language and Literature Education Study Program, semester III at the Faculty of Teacher Training and Education (FKIP) Islamic University of Malang. The research focuses on increasing group proficiency in compiling infographics of journalistic terms through the Didi Manis learning model. This research design uses one-cycle Classroom Action Research (PTK). The results of this study prove that students get a more complex learning experience because they are in two different groups. The results of the infographic made by the group also showed good results with an average value above 80.